DISINTEGRATION AND EMERGENCE OF A NEW TYPE OF DESTRUCTIVE MAN IN UKRAINIAN AND RUSSIAN LITERATURE OF THE LATE 20th – EARLY 21st CENTURY - Kateryna O. Hodik (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article is devoted to the analysis of the concept of devilry in the postmodern works of the late 20th – early 21st century. Particular attention is focused on the following texts: the novel by Sergei Zhadan “Voroshilovgrad”, Lyubka Deresh “Adoration of the Lizard”, S. Minaev “Dukhless. The Story of a Fake Man”, V. Pelevin “Chapaev and Pustota” (aka “Clay Machine Gun”). The aim of the work is to define a new type of destructive person in the Ukrainian and Russian literatures of the mentioned period. The features of assimilation of this concept, features of its transformation in the latest Ukrainian literature are considered. The analysis of the texts has led to a number of conclusions. First, in the mentioned literary works, the concept of devilry is not only presented, it is one of the important driving forces of the plot. In the novel “Voroshilovograd” by S. Zhadan and “Chapayev and Pustota” (aka “Clay Machine Gun”) by V. Pelevin, he predetermines the formation of the hero. Secondly, this concept forms a link between contemporary texts and literary tradition. We can trace which of its important features have been taken over by contemporary authors and which have been rejected. Thus, both Ukrainian and Russian authors preserve the basic binomial structure of demonism with demons of a higher and lower order, they continue to exploit precisely the name of Dostoevsky and the symbolic concepts from his works. However, writers are developing new strategies for dealing with a destructive union, in particular, freeing from it through memory restoration. Thirdly, when analyzing such works, special attention must be paid to the confrontation between the personality and external forces that provoke its transformation and rejection of the human appearance. This can be traced in both the Russian and Ukrainian versions of the concept. Summarizing the above, we can say that the type of intellectual who rises above the crowd is realized in Ukrainian literature. This is the variation of destructiveness formed in the twentieth century. However, it will unfold differently. In particular, the Nietzschean question of the superman will be removed in the 21st century. The texts of modern Ukrainian literature show that the new hero will still have to prove his humanity, and only after that – the right to supremacy, uniqueness, belonging to the governing structure. The concept of a spiritless person (“Spiritless”) is realized in Russian literature. It is likely that the hero of modern times will be closely associated with advertising, the media as tools for managing society. In this case, the understanding of this type of characters will be accompanied by apocalyptic visions, which in one way or another will be realized in modern literature (here the author agrees with M. Berdyaev on the significant role of apocalyptic motives in the culture). In general, a detailed review of the works suggests that “demonic” in the 21st century is undergoing another transformation and will continue to work for the needs of the national culture. How this will happen, what mechanisms will affect its rethinking, and what kind of rice will acquire a new type of hero, is a topic for further research.